Pemberdayaan Petani Lokal melalui Digital Marketing di Desa Karang Anyar Kecamatan Beringin Kabupaten Deli Serdang - Jamaluddin Jamaluddin; Renny Lubis; Susan Novrini; Pinondang Nainggolan; Reyndi Fernando Santoso (Yayasan Literasi Sains Indonesia, 2025)
This community service program was implemented with the aim of improving the skills of local farmers in Karang Anyar Village in utilizing digital marketing to expand the market for agricultural products. The main challenges faced by partners were limited technological understanding, dependence on middlemen, and limited market access, which made product prices less competitive. Activities were carried out through training, mentoring in digital content creation, introduction to e-commerce, and implementation of social media-based marketing strategies. Methods used included an extension approach, hands-on training, and performance evaluation through online sales monitoring. The results of the program showed an increase in farmers' understanding of smartphone use, 78% of participants were able to create product photo content, and 65% had registered on digital platforms such as Facebook Marketplace, WhatsApp Business, and Tokopedia. Furthermore, sales increased by an average of 20% within one month of the program. In conclusion, digital marketing has proven to be an effective strategy for increasing the competitiveness of local farmers in the digital economy era. This program is recommended to be continued through ongoing partnerships with village officials and farmer groups.